The Hague and Brussels. Organisation of building projects of the courts 1590-1630 (Bulletin KNOB, 1999)
The study of the structural organization of the building projects at the Brussels court during the reign of Archdukes Albrecht (1599-1622) and Isabella (1599-1633) on the one hand and the court of The Hague during Maurits of Nassau (1585-1625) on the other, revealed both parallels and remarkable differences. Undoubtedly the similarities are due to their common political-historical background until 1581, but even betore the separation differences already emerge.The Hague is just a count's court - and only later a princely court - in the periphery of the Spanish Kingdom, unlike the royal residence in Brussels, which operates as the political centre of the Netherlands. Consequently, Maurits of Nassau lacked an equivalent tradition of court architects, as it developed in Brussels, where the court architects and engineers hold the statute of officers of the court. They play an important part in archducal politics and have ample powers and extensive artistic responsibility.By and large, the administrative organization of the building projects is similar at both courts: the stewards and inspectors of the Nassau Domains see to a good administration and management of the buildings. The architect is responsible for the plans and in charge of recruitment.The architects avant la lettre of Honselersdijk and Nieuburg occupy a well-established position in the building office, because each of them are or become ‘stadsfabrycq’. Here lies a second contrast with the Brussels court, for since the early 16th century court artists had emancipated themselves from the urban building industry.Towards the end of the 16th century out of sheer necessity a separate office is founded in Brussels, which solely occupies itself with the court works. It is in close contact with the court architect and the supervisor of the works. Whether the different organization of the court works affected the aspect of the architecture was not dealt within this article.First and foremost, the reference material is divided in an unbalanced manner. After all, Maurits's priorities are not so much an architectural-propagandist but rather a military programme. Moreover, the situation of the court differs greatly: the Archduke and Archduchess are oriented towards the Spanish-Habsburg and the imperial courts with their international aura, whereas at that time the Prince of Orange is only familiar with a limited court life.Not until 1634 does a change occur in the situation in The Hague when Simon de la Vallée is appointed ‘architect of His Royal Highness's buildings’ by Frederik Hendrik. However, an essential equivalent of the Brussels court architect does not appear until the appointment of Pieter Post, who is appointed ‘painter and architect ordinaris’ by the prince on February 9, 1646. From that moment Post belongs to the domestic officers. After the death of Frederik Hendrik he remains in the service of his successor, Willem II, and his service is continued just as in Brussels.